Otolith morphometrics for growth and conservation assessment of endangered Napoleon wrasse (Cheilinus undulatus) in Sabah, Malaysia - EKO HENDRI GUNAWAN; CHING FUI FUI; AUDREY DANING TUZAN; NAZIA ABDUL KADAR; FITTRIE MEYLLIANAWATY PRATIWY; IBNU DWI BUWONO; SHIGEHARU SENOO (Society for Indonesian Biodiversity, 2025)
Abstract. Gunawan EH, Fui CF, Tuzan AD, Kadar NA, Pratiwy FM, Buwono ID, Senoo S. 2025. Otolith morphometrics for growth and conservation assessment of endangered Napoleon wrasse (Cheilinus undulatus) in Sabah, Malaysia. Biodiversitas 26: 5770-5779. The endangered Napoleon wrasse (Cheilinus undulatus) plays a vital role as a carnivorous fish in coral reef ecosystems. However, it faces severe threats from overfishing and habitat degradation, necessitating evidence-based conservation strategies. This study assessed growth pattern, biological condition, and size structure by integrating fish morphometric and otolith metrics from 41 specimens collected in Eastern Sabah, Malaysia. Fish total length from 27.51 to 103.88 cm (mean SD = 35.28±11.72 cm) and body weight from 330.24 to 19400.85 g (mean SD = 757.32±2934.41 g). Linear regression revealed a near-isometric length-weight relationship (b = 3.062, 95% CI [2.904, 3.219], r² = 0.975, p<0.001), indicating proportional growth with robust model fit. Fulton's condition factor (K) was stable across size classes (range: 1.319-2.089, mean ± SD: 1.695±0.189), showing no significant differences (ANOVA, p>0.05) and suggesting consistent physiological health amid environmental pressures. Size distribution was skewed toward juveniles and intermediates (<40 cm, 78% of samples), highlighting potential recruitment overexploitation. Otolith metrics demonstrated strong predictive power, with otolith weight correlating highly with fish length (r² = 0.784, p<0.001) and weight (r² = 0.766, p<0.001), validated through cross-validation (CV-MSE comparable to in-sample MSE) and residual diagnostics confirming normality, homoscedasticity, and independence. These findings highlight the vulnerability of C. undulatus populations in Eastern Sabah, which juvenile exploitation may undermine recovery potential. Otolith-based metrics provide cost-effective, essential baseline data for stock assessments, enabling precise monitoring of growth and demographics. For future conservation management, this supports implementation of minimum size limits, enhanced marine protected areas, and community-led surveillance, fostering sustainable recovery of this iconic species and reef biodiversity.